Reformulation Of The Effect Of Hybrid Learning Class Management On Critical Thinking Learning (Journal of Namibian Studies : History Politics Culture, 2023)
The education system in Indonesia, which continues to experience development from a conventional system, has shifted to an all-digital system. Where in the past the teaching and learning process only took place in the classroom, but now the teaching and learning process is no longer bound by space and time. This is due to the situation of the COVID- 19 pandemic, the teaching and learning process system switches to the Hybrid Learning system. Hybrid Learning is using learning that combines various approaches, namely face- to-face learning, computer-based learning, and online-based learning (internet and mobile). The ability to think critically or critically thinking is one of the most important abilities to be mastered by humans today. Learning should be directed to train students to be able to think critically about a problem. Learning that teaches memorization is better starting to be replaced by analyzing and providing logical solutions. This study aims to determine how the factors that affect Critical Thinking and Hybrid Learning, in PAK learning. Researchers are trying to get data related to student test results about Christian Religious Education. The results of data analysis show that there is a positive and significant influence on Hybrid Learning Class Management on the Critical Thinking of Students in Christian Religion & Morals Education Subject Class X SMA N 1 Plus Matauli Pandan in the 2021/2022 Academic Year. So, from the calculation results obtained Fcount = 34.38 which means it is greater than Ftable = 3.97, then based on the hypothesis testing Ha = Fh (34.388>3.97). This shows that Ha is accepted and Ho is rejected, which means that there is a positive and significant influence between Hybrid Learning Class Management on Critical Thinking of Students in Christian Religious Education Subject Class X SMA N 1 Plus Matauli Pandan for the Academic Year 2021/2022.